MINERALOGY, GEOCHEMISTRY, AND SEQUENTIAL EXTRACTION EXPERIMENT OF REE IN WEATHERED ANGGI GRANITE, MANOKWARI REGENCY, WEST PAPUA, INDONESIA - Ega Gita Prasastia; Lucas Donny Setijadji; I Wayan Warmada (Journal of Applied Geology, 2015)
This research objective is to identify geochemical andmineralogical characteristics of Rare earth elements(REE) in the weathering products of Anggi Granite, which is located in Manokwari Regency, WestPapua, Indonesia. The research is conducted on 7samples of fresh rocks and 7 samples of weatheredrocks of Anggi Granite. The research analysis consists of petrography, XRD, XRF, and sequential extraction experiment, supported by secondary dataand references. Anggi Granite is S-type and peraluminous granite that contains zircon, monazite andapatite as a rare earth bearing minerals. Weathering products of Anggi Granite do not have a significant enrichment of REE, even some of the samplesare depleted in REE. REE in weathered Anggi Granite are dominantly present in the primary minerals,mostly in zircon and monazite. Extractable formof geochemical fractions include crystalline Fe-oxideoccluded fraction (ilmenite, hematite and goethite),and ion-exchangeable (illite, kaolin and chlorite).Enrichment of REE in the weathered Anggi Granite is influenced by the presence of resistant REEbearing minerals, in the forms of zircon and monazite, degree of weathering related to the presenceof secondary minerals, and other factors such as pHand Eh